An Investigation of the Relationship between Economic Components and the Increased the Resilience of Local Communities in Birjand - Saeb, Samaneh; Bostani, Maryam Karimian; Anvari, Mahmoudreza (International Journal of Psychosocial Rehabilitation, 2020)
Examining the issue of societies’ social vulnerability to environmental hazards can reduce both human suffering and economic loss. More than half of the world’s population lives in urban areas, and many of them live in areas with potential risks and accidents. Birjand is the capital of South Khorasan province with various adjacent faults that have provided conditions for seismicity in this city. This research has investigated the relationship between economic components and increasing the resilience of local communities in this city with a descriptive and analytical approach. Due to the spatial distribution of vulnerabilities is located in the suburbs and northern neighborhoods of the city and over time have achieved a relatively better economic situation, but the results of the study and evaluation of the economic vulnerability of Birjand neighborhoods to earthquakes show that the satisfaction of the new generation with life is very low. The reason for this is that over time the overall living conditions and absolute poverty have decreased but relative poverty is increasing.